Gene expression is associated with virulence in murine macrophages infected with Leptospira spp - de Araújo, Erivelto Corrêa [UNESP]; Garcia, Leandro Encarnação [UNESP]; Araújo, Matheus Janeck [UNESP]; Oliveira-Junior, Itamar Souza; Arnold, Daniel Robert [UNESP]; Lopes, Flavia Lombardi [UNESP]; Marinho, Márcia [UNESP] (Public Library of Science (PLoS), 2019)
Leptospira genus contains species that affect human health with varying degrees of pathogenicity. In this context, we aimed to evaluate the differences in the modulation of host gene expression by strains of Leptospira varying in virulence. Our data showed a high number of differentially expressed transcripts in murine macrophages following 6h of infection. Leptospira infection modulated a set of genes independently of their degree of virulence. However, pathway analysis indicated that Apoptosis, ATM Signaling, and Cell Cycle: G2/M DNA Damage Checkpoint Regulation were exclusively regulated following infection with the virulent strain. Taken together, results demonstrated that species and virulence play a role during host response to Leptospira spp in murine macrophages, which could contribute to understanding the pathogenesis of leptospirosis.